Niepomijalność podmiotowości człowieka i niepomijalność misji administracji publicznej w służbie dobru wspólnemu (dobru osobowemu) - Blicharz, Jolanta (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
There are three serious arguments that the concepts of common good and dignity as a dimension of human subjectivity condition each other and cannot be developed separately. First, the common good is based on the recognition of human dignity. Secondly, the frustration of the realization of the common good by the state and the law undermines human dignity. Thirdly, the emphasis on human subjectivity (dignity) and the subordination of social institutions to the common good makes it possible to distinguish the objective of state action from the means instrumental with regard to this objective.
Keywords: dignity of (a) human being(s); public administration; country; the common good